2017
DOI: 10.1016/j.amsu.2017.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of submucosal epinephrine injection for the prevention of postpolypectomy bleeding: A meta-analysis of randomized controlled studies

Abstract: BackgroundBleeding is the most common major complication following colonoscopic polypectomy. The purpose of this study is to evaluate whether submucosal epinephrine injections could prevent the occurrence of postpolypectomy bleeding.MethodThe dataset was defined by searching PubMed, EMBASE, Google Scholar, and the Cochrane database for appropriate randomized controlled studies published before April 2015. A meta-analysis was conducted to investigate the preventative effect of submucosal epinephrine injection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
2
11
0
1
Order By: Relevance
“…However, the delayed bleeding rate in the non-epinephrine and epinephrine groups was not significantly different (both 6 %). A recent meta-analysis of six randomized controlled trials showed that epinephrine injection significantly reduced the occurrence of early bleeding but not of delayed bleeding 26 . Epinephrine has a short duration of action of 5 to 10 minutes; therefore, we considered that epinephrine injection would not be effective for reduction of delayed bleeding of gastric ESD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the delayed bleeding rate in the non-epinephrine and epinephrine groups was not significantly different (both 6 %). A recent meta-analysis of six randomized controlled trials showed that epinephrine injection significantly reduced the occurrence of early bleeding but not of delayed bleeding 26 . Epinephrine has a short duration of action of 5 to 10 minutes; therefore, we considered that epinephrine injection would not be effective for reduction of delayed bleeding of gastric ESD.…”
Section: Discussionmentioning
confidence: 99%
“…ESGE guidelines recommend the use of diluted epinephrine before hot-snare polipectomy of large pedunculated polyps (head size ≥ 20mm or stalk width ≥ 10mm), but there is no mention regarding the systematic need for its injection in other types of lesions. A recent meta-analysis concluded that the application of submucosal epinephrine injection before resecting larger polyps (≥ 20 mm) as a routine procedure is helpful to reduce the occurrence of early postpolipectomy bleeding[35]. However, in this meta-analysis injection of diluted epinephrine was not shown to significantly reduce the risk of delayed postpolipectomy bleeding.…”
Section: Adjuvantsmentioning
confidence: 90%
“…A recent meta-analysis of three randomized controlled studies[64] that compared the efficacy of epinephrine injection and mechanical hemostasis in postpolypectomy bleeding in patients with pedunculated polyps over 20 mm demonstrated that prophylactic treatment with mechanical hemostasis is more effective than epinephrine injection for preventing overall postpolypectomy bleeding (2.2% vs 6.3%) and early postpolypectomy bleeding (1.1% vs 4.5%). The rate of delayed postpolypectomy bleeding was 1.9% in the epinephrine group and 1.1% in the mechanical group, and their implementation was not found to significantly affect the rate of delayed postpolypectomy bleeding (OR = 0.58, 95%CI: 0.13, 2.49; P = 0.46) without significant heterogeneity between the studies ( P = 0.94, I 2 = 0%).…”
Section: Challenges In Endoscopic Resection Techniquesmentioning
confidence: 99%
“…Different risk factors for postpolypectomy complications, such as old age (older than 65 years of age), underlying diseases (cardiovascular or chronic renal disease), anticoagulant use, polyp size > 10 mm, a stalk size > 5 mm, polyps located on the right side of the colon, malignant polyps, use of cutting mode and low-volume endoscopists, have been described[47,64-67].…”
Section: Challenges In Endoscopic Resection Techniquesmentioning
confidence: 99%